Improving the production and managerial performance of tempeh chip MSMEs - Setiawan, Ferry; Wicaksono, Dhimas; Rizki, Ikbal; Hillal, Raden Fatchul; Widagdo, Djoko; Mahendra, Dimas Aditya (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2024)
The Community Service Program of STTKD Lecturers is funded by the Directorate of Research and Community Service of the Ministry of Education and Culture due to the problems faced by Micro, Small, and Medium Enterprises (MSMEs) of tempeh chips brand "Tempe Krees", including; low production capacity, inability to meet market demand, poorly organized managerial processes, and unattractive product branding that hinder online market penetration. The solution provided by the Community Service Team in the technological field is to increase the productivity of tempeh chips by using appropriate technological equipment, such as a soybean skin separator machine, tempeh slicing machine, and oil separator machine. In the managerial field, management and marketing training is conducted to reach a wider market share and improve packaging design to increase product branding in order to penetrate the online market. The result of this program is that the managerial competence of the partners has improved, as can be seen from the results of the posttest which has a better value than the pretest results. With the application of appropriate technology equipment, the production of tempeh chips increased from 50-55 pieces @ 250 grams per day to 100-110 pieces @ 250 grams per day. Production costs have decreased from Rp11,025 to Rp9,932, so the profits of MSME partners have increased from before. The next step after this community service is to encourage partners to penetrate the modern market so that partner businesses can develop well and trigger economic growth in the community around the location of MSMEs.